A Novel Compact CPW Multi-StopBand Filter with DGS Integrating Circular Ring Resonator - Latrach, Mohamed (Transactions on Engineering and Computing Sciences, 2017)
A novel and compact multi-band stop filter with good selectivity and wide upper pass band performance with good rejection based on defected ground structure (DGS) integrating a circular ring resonator to suppress undesired spurious bands frequency or harmonics in microwave and millimeter wave circuits is proposed. The presented filter has a compact size because the circular ring resonator is integrated in DGS, the both of them are etching in the ground plane.